Spatial Games: A Learning Experience From Multiple Intelligence Theory to Lefebvre's Triangular Space Dialect, in Architectural Design Education - Sagiroglu, Pinar Meliha (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
Students who are trying to adapt themselves to architectural design education are having some problems because they are used to the Turkish secondary education system's doctrines and discipline. The reason for these problems is that different mental skills are needed for the architectural design education and the secondary education system. Multiple Intelligence Theory as conceived by Howard Gardner states that different mental skills actualize in different parts of the brain. Spatial Games is an intelligence practice, which encourages young minds to understand and define space. The game connects Logical- Mathematical intelligence and Visual- Spatial intelligence. This study handles space as a summation of physical realities (such as height, size, light, and heat) which are not measured but predicted during the game. Players relate spaces through proportional relationship. This helps players to perceive these physical properties of spaces and is fictitiously based on the process of predicting, designing, and examining, which is parallel to the course that Armstrong offered to facilitate by passing on from one intelligence to other. As a result, there is a connection to this formation to Spatial Triad of Lefebre, which is formed
Keywords: Multiple intelligence theory; space; architectural design education; game; spatial triad; Architecture